Project of VEPP-2000 electron-positron collider - Shatunov, Yu.M.; Evstigneev, A.V.; Ganyushin, D.I.; Ivanov, P.M.; Koop, I.A.; Kuzminykh, V.S.; Lysenko, A.P.; Mezentsev, N.A.; Mityanina, N.V.; Nesterenko, I.N.; Otboev, A.V.; Perevedentsev, E.A.; et al. (Вопросы атомной науки и техники, 2001)
The status of VEPP-2M collider is presented. Implementation of Round Colliding Beams (RCB) concept in the new collider VEPP-2M is outlined, potential advantages of RCB over the flat colliding beams are discussed. The main desing parameters and features of this VEPP-2000 collider are reported.